Refinement of job crafting scale: Motivation, work engagement and job performance among Thai healthcare professionals - Rochanadumrongkul, Pichaya; Jarunratanakul, Prapimpa (Asia-Pacific Journal of Science and Technology, 2022)
Job crafting is the method whereby employees to reframe their jobs including physically (changing the form of the task), socially (changing interactions with colleagues), and cognitively (changing ways of perceiving the job). The purpose of this study was to develop and validate job crafting measures related to the level of motivation, work engagement and job performance in Thai healthcare professionals using structured interviews and structured equation model (SEM). A qualitative method using the interview (n=20) was employed to extract employees’ experiences of crafting their job and explore additional dimensions of job crafting. The results of the interview revealed an additional dimension of job crafting, namely "humor” for the Thai Job Crafting Behavior scale (JCB) (physical crafting, relational crafting, cognitive crafting and humor). In the quantitative method, the content validity and construct validity; Exploratory Factor Analysis and Confirmatory Factor Analysis (EFA and CFA) were used to meet the validation of the additional dimension in the Thai JCB measurement model. Thai JCB was also given empirical support through concurrent and convergent validation. Moreover, the results of the Thai JCB structural model and related variables (i.e., motivation, work engagement, and job performance) fit well with the observed data in the expected direction. The findings can be beneficial to organizations by providing an understanding of job crafting behavior among Thai healthcare professionals, which can consequently lead to increased work motivation, work engagement, and job performance. The implications and recommendations of Thai JCB are discussed.